Hormigas en cultivos de naranja (Citrus sinensis L. Osbeck) de la costa Caribe de Colombia (2013)
This article describes the database of the ant fauna associated with orange crops on the Caribbean coast of Colombia. The study was carried in the departments of Bolivar, Cordoba, Cesar and Magdalena, in crops of 38 farms in 13 municipalities. In all cultivations, the ants were collected by transects of 50m each with five sampling stations separated by 10 m, at each one three sets of sampling techniques were applied: direct capture (manual), pitfall traps and Winkler sacks. A total of 3119 samples were obtained, distributed into eight subfamilies, 44 genera and 122 species. As expected Myrmicinae subfamily was the one that presented the highest richness (65 species) and capture rate (63,45%). The two most frequent were Ectatomma ruidum and Crematogaster abstinens appearance with a percentage of 13,34% and 8,62% respectively. The database reflects a great diversity in orange crops with a large presence of groups considered important as biological controls including hunting ants and cryptic myrmicines.